Richard J. Walter: Politics and Urban Growth in Buenos Aires: 1910-1942 - Lund, Julius (Tidsskriftet Antropologi, 2019)
Richard J. Walter: Politics and Urban Growth in Buenos Aires: 1910-1942 Anmeldes af Julius Lund